Optimizing Cost and Performance of Cloud versus on Premises in Digital Wallet Start up - Dion Kurniawan; Endroyono Endroyono (Dinasti International Journal of Education Management And Social Science, 2024)
In the context of the rapid growth of the fintech industry in Indonesia, the study explores the choice of IT infrastructure in particular between on premise and cloud in digital wallet fintech start-ups to improve cost efficiency. With a lack of detailed information in the literature about the critical role of infrastructure in the development of fintech, the study uses Mixed Methods The Convergent Parallel Design to provide in-depth insights into the impact of infrastructural decisions on operational and financial efficiency. The findings show that the adoption of cloud infrastructure, chosen for its scalability, flexibility, and cost efficiency, is significant in reducing operating and maintenance costs, while strengthening market positions. However, the decision also calls for serious consideration of security aspects, data privacy, and regulatory compliance. The findings provide important contributions for policymakers, regulators, and industry stakeholders in understanding the importance of data security strategies and company-specific needs in selecting IT infrastructures. In conclusion, choosing the right IT infrastructure is key to reducing costs and supporting sustainable growth in the fintech sector, especially for digital wallet start-ups.